A Qualitative Exploration Into The Role Of Organisational Or Institutional Reputation And Integrity In The Theory And Practice Of Public Administration In South Africa: A Drive Towards Creating A Credible, Sustainable And Democratic Public Administration - Peter Lebosa Bogopane (European Scientific Journal, ESJ, 2016)
This manuscript deals with and reports on the qualitative exploration of and analysis into the most pertinent, yet severely ignored concept of “institutional/organisational reputation and integrity” in public administration and management. The study was inspired and motivated by the fact that even though theme plays a significant role in influencing trust and support in our public and private entities alike, very little has been written about the concept. The article commences by providing a general theoretical background to and definition of this theme. It also presents a brief overview on the roles of and the importance this largely neglected concept has in enhancing, consolidating, and improving the position of governance and service delivery of both our public and private entities. More significantly, the author identifies four (4) phases/facets/dimensions that are associated with institutional/organisational reputation and integrity, namely: Performative reputation; Moral reputation; Procedural reputation; and Technical reputation, and uses them as the hallmarks for this qualitative exploratory analysis. Methodologically, the study employs a qualitative phenomenological and empirical research paradigm and design, to understand the functionality and performance of institutional/organisational reputation and integrity within the context of South African public and private entities. Qualitative data collection and gathering methods such as (Participant observation; In-depth interviewing; Document study; and Case study) and qualitative data analysis and interpretation techniques such as (Qualitative Content analysis; and qualitative Case analysis) are used to collect and gather data and to analyse and interpret data respectively. The population of the study is described as comprising of all public and private entities serving the people and doing business in South Africa. A judgmental and/or purposive sampling technique is employed as a way of selecting study participants. Findings will be arrived at, and on their basis, recommendations will be clearly provided and articulated.